Fiscal Policy and Long-Run Growth - Tanzi, Vito.; Zee, Howell (Washington, D.C. : International Monetary Fund, 1996)
This paper discusses in a systematic and comprehensive way the existing literature on the relationship between the growth of countries' economies and various public finance instruments, such as tax policy, expenditure policy, and overall budgetary policy, from the perspectives of allocative efficiency, macroeconomic stability, and income distribution. It reviews both the conceptual linkages between each of the instruments and growth and the empirical evidence on such relationships. It broadly concludes that fiscal policy could play a fundamental role in affecting the long-run growth performance of countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet